The Effect Of Debt To Equity Ratio (DER) And Return On Equity (ROE) On Price Book Value (PBV) In PT. Pakuwon Jati Tbk Period 2014-2023 - Diana, Riska Puspita; Sari, Widya Intan (Fin Sinergy: Jurnal Manajemen Keuangan, 2025)
This research aims to find out The effect of Debt toEquity Raio (DER) and Return on Equity (ROE) on Price Book Value (PBV) at PT. Pakuwon Jati Tbk for the 2014- 2023 period. The research method used is a quantitative method with descriptive analysis techniques. The data used is secondary data in the form of annual financial statements on PT. Pakuwon Jati Tbk, the data was tested using the Statistical Product Service and Solution (SPSS) application program versio 27.0. The results of this research show that simultaneously Debt to Equity Ratio (DER) and Return on Equity (ROE) have a significant effect on Price Book Value (PBV). This is shown by the Fcal value of 57.630 > F table 4.74 and significant 0.001 < 0.05. The value of the adjusted R2 determination coefficient of 0.943 shows that the influence of Debt to Equity Ratio (DER) and Return on Equity (ROE) on Price Book Value (PBV) is 94.3% and the remaining 5.7% is influenced by other variables outside the study.